Entrepreneurial competencies and involvement of children in family businesses - Mendoza, Catherine Julia
This is a descriptive study that used qualitative and quantitative methods. For the first part, a standardized Personal Entrepreneurial Competency (PEC) Test was administered to the CFB's in order to determine their current PEC based on their PEC's Test scores. For the second part, which described the level involvement of the CFBs, a personal interview was conducted. The final LOI scores of the CFB's has a range of 6 - 14. For the PEC score, there is a wide range of 129 - 189. The CFB's level of family business involvement varies from one task to another. The CFB's involvement was described in four different ways: LC-LD or Low Complexity - Low Duration, LC-HD or Low Complexity - High Duration, HC-LD or High Complexity - Low Duration, and HC-HD or High Complexity - High Duration. Based on a one-tailed Pearsons Correlation test, there is a weak negative and not significant correlation between the level of involvement and personal entrepreneurial competency of the respondents.